Local time-varying topology identification of network with unknown parameters based on adaptive synchronization. (2nd October 2018) - Ren, Hai-Peng; Tian, Kun; Zhou, Ren
ABSTRACT: The network with some or all of characteristics including self-organization, self-similarity, attractor, small world and scale-free is referred to as a complex network. A complex network might demonstrate various uncertainties, such as the unknown node kinetics and the unknown network topology. The network topology identification using the observing output data of the network is a crucial step for complex network analysis, which is of great importance to understand the networks' properties and regulate network. In this paper, the output variable is used to drive the response network to identify partial time-varying topology of the drive network with unknown parameters. The synchronization between the response network and drive network and the successful identification are guaranteed by the Lyapunov stability theorem. The feasibility of the proposed method is demonstrated using two examples. Ovo je primjer sažetka. Ovo je primjer sažetka. Ovo je primjer sažetka. Ovo je primjer sažetka. Ovo je primjer sažetka. Ovo je primjer sažetka. Ovo je primjer sažetka. Ovo je primjer sažetka. Ovo je primjer sažetka. Ovo je primjer sažetka. Ovo je primjer sažetka. Ovo je primjer sažetka. Ovo je primjer sažetka. Ovo je primjer sažetka. Ovo je primjer sažetka.